Implementasi Problem Based Learning (PBL) Terintegrasi Biomagz untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 2 Bondowoso - Farizatul Qamariyah; Dewi Kartika Sari; Ali Usman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The potential of students in education is supported by learning that involves students actively in learning. Problem Based Learning can provide learning that involves students both physically and mentally. Biomagz as a learning media is designed in an attractive way to help learning become active. Learning through integrated Biomagz Problem Based Learning is expected to involve students, so as to improve student learning outcomes. This type of research is Classroom Action Research. The subjects were students of class XI MIA 8 at Senior High School 2 Bondowoso for the 2022/2023 academic year. Data collection through the post-test results. The results showed that there was an increase in student learning outcomes. Individually, there was an increase in the average learning outcomes, which in the pre-cycle the average value was 72.963, cycle I 76.667, and cycle II 89,259. Learning outcomes also increased classically, in which the percentage in pre-cycle was 18.51%, cycle I 70.37%, and cycle II 96.30%. Based on these results it can be concluded that the implementation of Problem Based Learning integrated with Biomagz was able to improve the learning outcomes of students in class XI MIA 8 SMA Negeri 2 Bondowoso for the 2022/2023 Academic Year.